الدمج المدرسي للطفل التوحدي من وجهة نظر معلمي الابتدائي: دراسة ميدانية على معلمي الطور الابتدائي بمدينة تلمسان - الجزائر - هوارى، أحلام Hawari, Ahlam; شويخي، آمال (جامعة العربي التبسي تبسة - مخبر الدراسات الإنسانية والأدبية, 2021)
تهدف الدراسة الحالية إلى التعرف على إمكانية الدمج المدرسي للطفل التوحدي في الأقسام العادية من وجهة نظر معلمي الطور الابتدائي، لهذا الغرض تم الاعتماد على مقياس "سناء محمد حسن دراوشة" كأداة، أجريت الدراسة على عينة مكونة من 60 معلم ومعلمة في المدارس الابتدائية بمدينة تلمسان. تم التوصيل إلى مجموعة من النتائج منها: لا توجد فروق في وجهة نظر المعلمين نحو إمكانية الدمج المدرسي للطفل التوحدي باختلاف الأقدمية المهنية للمعلم في جميع أبعاد مقياس الدمج المدرسي، كما أنه لا توجد فروق في وجهة نظر المعلمين نحو إمكانية الدمج المدرسي للطفل التوحدي باختلاف التخصص الدراسي للمعلم في جميع أبعاد مقياس الدمج المدرسي.
The present study aims to identify the possibility of integration school children with autism in regular section from for the teachers’ point of view, the researcher used as a tool the questionnaire for «Sana Mohammed Hassan Darawsheh», the instrument of research were applied on a sample composed of 60 teachers in primary school. A set of results were reached, including: There are no differences in the teachers ‘viewpoint towards the possibility of school integration for the autistic child according to the professional seniority of the teacher in all dimensions of the school integration scale, and there are no differences in the teachers’ viewpoint towards the possibility of school integration for the autistic child according to the different academic specialization. For the teacher in all dimensions of the School Inclusion Scale.
Keywords: الدمج التعليمي -- أطفال التوحد -- التعليم الابتدائي